Blended Learning, The International Chinese Learning Trend In Post-Pandemic Era - Nanda Lailatul Qadriani (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
In the early days of the Covid-19 pandemic, Chinese online learning faced many challenges, including (1) poor internet connection and high internet costs; (2) low computational literacy of teachers; (3) limited interaction between teachers and students; (4) inappropriate teaching materials and methods; and (5) the lack of student discipline and the difficulty of providing assessments. However, these challenges have turned into opportunities for the rapid development of online Chinese learning over time. Academics in China predict that online Chinese learning will be maintained in the post-pandemic era, the blended learning will become a learning trend that is applied globally. This research is descriptive qualitative research with data collection techniques through literature study method and Forum Group Discussion (FGD).  The result of this study is a description of the solution to the challenges of Chinese online learning globally during the pandemic, blended learning, and its implementation strategy in the post-pandemic era based on the “Chinese Proficiency Grading Standards for International Chinese Language Education” issued in 2021.